Dietary Self-Control Is Related to the Speed With Which Attributes of Healthfulness and Tastiness Are Processed. (February 2015) - Sullivan, Nicolette; Hutcherson, Cendri; Harris, Alison; Rangel, Antonio
We propose that self-control failures, and variation across individuals in self-control abilities, are partly due to differences in the speed with which the decision-making circuitry processes basic attributes, such as tastiness, versus more abstract attributes, such as healthfulness. We tested these hypotheses by combining a dietary-choice task with a novel form of mouse tracking that allowed us to pinpoint when different attributes were being integrated into the choice process with temporal resolution at the millisecond level. We found that, on average, tastiness was processed about 195 ms earlier than healthfulness during the choice process. We also found that 13% to 39% of observed individual differences in self-control ability could be explained by differences in the relative speed with which tastiness and healthfulness were processed.